IMPLEMENTASI METODE DISKUSI TERHADAP PENINGKATAN PEMBELAJARAN KITAB-KITAB SALAF - Ma?duali, Firman; Siskandar; Sunhaji, Akhmad (Fakultas Tarbiyah, Institut PTIQ Jakarta, 2019)
The results found in this study are: First, the discussion method is carried out in the form of questions and answers between teachers and students when teaching the bandongan model. In this discussion each group discusses with various academics literature. This discussion is sometimes made in the SSC (Santri Study Club) model which follows the ILC (Indonesia Lawers Club) model. Besides the discussion method is also used in the form of presentations, each student is assigned to present a discussion theme in a book of salaf then discuss together the purpose of the contents of the book. Second, the discussion model in the pesantren khatamun nabiyyin is different from the discussion model in the teaching and learning process in general. If the discussion is generally carried out freely with free conclusions as well, then the discussion at the Khatamun Nabiyyin pesantren is conducted in a guided manner to explore a particular discussion, with conclusions that are free but still in accordance with the knowledge taught by the kyai or cleric.